Konstitusionalitas dan Model Pendidikan Karakter Bangsa Pasca Putusan Mahkamah Konstitusi - Bayu Dwi Anggono (Jurnal Konstitusi, 2014)
Constitutional Court Decision No. 100/PUU-XI/2013 stated that Pancasila as a basic state declared in the the 1945 preamble can not be equated with the 1945 Constitution, Unity in Diversity, and the Unitary State of Indonesia declared as the pillars of the nation and state as cited in the Article 34 paragraph (3b) letter a. Considering the benefits of the nation’s effort to build a character, the Constitutional Court declared constitutional effort of political parties and other state agencies  that carry out political education through the dissemination of Pancasila, the 1945 Constitution, Unity in Diversity. The Court sets a model of character education necessary to be developed which is not limited in the for pillars but it includes some other aspects such as the state of law, sovereignty, an insight of archipelago, national defense, and so forth. The government basically hold the primary responsibility for implementing character education for its citizens. Thus, the government needs to consider of alternatives to establish a special agency to formulate and implement effective national character  education.